Pengaruh Layanan Bimbingan Kelompok Terhadap Kemampuan Menjalin Relasi Pertemanan - Rohman, Yusuf Noor; Mugiarso, Heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
Abstract The purpose of this research was to get empirical data about effect of group guidance against ability to establish friendship relation of class VIII D Giriwoyo 1 junior high school, Wonogiri. This research used quantitative with an experimental design. The population was all student of class VIII D Giriwoyo 1 junior high school, Wonogiri. Sampling technique in this research was purposive sampling. Sample in this research were 10 students of class D. Instrument of this research were ability to establish friendship relation scale and handbook observation. The data analysis technique used descriptive percentage analysis and wilcoxon match pairs analysis. The result showed the ability to establish friendship relation of student before student are given group guidance service is in the average medium category (65,8%) and after obtaining group guidance service have an average in the high category (78,80%). Based on wilcoxon showed Zacount = 0 and Ztable = 8. The conclusion of this research  was guidance group service given  positive effect to ability to establish friendship relation student of class VIII D Giriwoyo 1 junior high school, Wonogiri.